Entre pipas, lutos, aprisionamentos e medicações : as peculiaridades na relação do Conselho Tutelar com as crianças encaminhadas pela escola - Fernandes, Priscila Valverde (2009)
This paper intends to study the particularities concerning the Tutorial Council and children that were sent by the schools from the city of Cariacica ES. It divides the field work in two main parts: the first was the contact with the ex-tutorial counselors from the period between 2005-2007 from the city of Cariacica; and the second with the children and their families that started a relation with the Tutorial Council sent by the school. It focuses this situation as a triangle in which the Council, the school and families-children could be considered as the three angles.The request was made in one of them, in this case – school; and a question rises concerning narratives and crossings that could be taken from the two other parts involved, families-children and the counselors. From this qualitative method, it flows through this way according to field variations. The theoretical reference works with authors that share the idea of a story that can be approached in a genealogical perspective, together with Foucault, that allows a vision of all kinds of knowledge existing in a determined space and social moment. Interviews were made with four counselors and for children and their families. From these interviews, it comes a relation marked by psychology, competent speech, proximity, familiarization and a strength field comes in which children is pushed to several places that produce and re-produce children’s behavior, considered as unacceptable.